Imaging x70 weld cross-section using electromagnetic testing. (September 2018) - Xu, Hanyang; Salas Avila, Jorge Ricardo; Wu, Fanfu; Roy, Matthew J.; Xie, Yuedong; Zhou, Frank; Peyton, Anthony; Yin, Wuliang
Abstract: Weld inspection is significant in manufacturing to improve productivity and ensure safety. During the welding process, steel microstructures experience complex transformations depending on welding conditions such as heat input, welding speed, component size and temperature, etc. Examining weld microstructures can reveal valuable information on its metallurgical, mechanical and electromagnetic properties. Electromagnetic (EM) testing is of great practical interest to characterise the weld microstructures in a non-destructive and expedient manner. In this paper, an experimental scanning method using a cup-ferrite enclosed T-R sensor has been devised to image the EM properties of a cross-section of an X70 steel submerged arc welding (SAW) specimen. These images show good correlation with the hardness testing and metallurgical information of the specimen. An approximate linear relationship was found between the EM signal and the hardness of the SAW of X70 steel weld. The scanning method can serve as a complementary tool for hardness testing without the need for sophisticated surface preparation.